IMPLEMENTASI BUILDING INFORMATION MODELING 4D (Studi Kasus: Proyek Lanjutan Pembangunan Gedung Kantor Sekretariat Daerah Kabupaten Tapin) - Husnul Khatimi; Kristnanda Floter Pardosi (Politeknik Negeri Jakarta, 2022)
Advanced Project of the Tapin District Secretariat Office Building located on Jalan Datu Suban, North Tapin, South Kalimantan is a reinforced concrete building project that only applies manual scheduling which is present in the form of S Curve. PUPR Ministerial Regulation Number 9 of 2021 states that every project should be based on Building Information Modeling (BIM). Therefore, this research discusses about the implementation of 4D BIM (scheduling) using Tekla on the advanced Project of the Tapin District Secretariat Office Building using Tekla to determine the use of BIM on scheduling obtained from contractors. This research method started from studying the software and the object to be modeled, collecting the data such as as-build, S Curve, budget plan. Data processing started from 3D modeling using Tekla Structures 2020, scheduling with Tekla Task Manager, and then 4D modeling with object representation. Scheduling made from the Budget Plan, S Curve, and interviews of related parties were input into the Tekla Task Manager with dependencies which were applied into the bar chart. The 4D model is created using the visual logic with the integration of the 3D model created by scheduling, the development planning stages can be displayed according to the reviewed date. It was concluded that Tekla Structures can be applied in scheduling the advanced project for the construction of the Tapin District Secretariat Office Building. Keywords: Scheduling, Tekla Structures, Tekla Task Manager, 4D Model, Advanced Project.